Green, Hybrid Synthesis and Characterization of Improved CQD with Antioxidant Properties for Biomedical Applications - Mishra, Dr. Manoj; Chahal, Dr. Preeti (Migration Letters, 2023)
Carbon quantum dots (CQDs) have recently gained attention as an auspicious material for various applications, focusing on the biomedical domain. This is primarily attributed to their exceptional optical characteristics, which set them apart from other materials. This study introduces a novel methodology for producing and analyzing advanced CQDs that exhibit superior antioxidant characteristics. The increased antioxidant capabilities of these CQDs are significant for their possible use in biological fields. This work uses CQDs, which are obtained by hydrothermal synthesis of lignin. To enhance their efficacy in biomedicine, these CQDs are subjected to surface modification using two distinct coumarins by applying microwave radiation, conferring upon them significant advantageous characteristics. Implementing this modification is of utmost importance to mitigate the constraints associated with CQDs’ inherent fluorescence quantum yield. The study begins by using hydrothermal synthesis to produce CQDs produced from lignin. Surface modification is conducted on the CQDs using two distinct coumarins with the assistance of microwave radiation. The HSC-ICQD approach utilizes a range of analytical methods, including Fourier-Transform Infrared Spectroscopy (FTIR), Atomic Absorption Spectroscopy (AAS), Nuclear Magnetic Resonance (NMR), and Transmission Electron Microscopy (TEM), to validate the achievement of effective modification. This work assesses the antioxidant capacity of the modified CQDs by quantitatively evaluating their abilities to scavenge superoxide and hydroxyl radicals. The findings underscore the appropriateness of using HSC-ICQDs in bioimaging, drug delivery, and therapeutic interventions within biomedicine. This study highlights the significance of using green synthesis methods to customize nanomaterials for biomedical applications, presenting encouraging prospects in nanomedicine.